The Minangkabau Women's Cultural Adaptation Strategy in Inter-Ethnic Marriage (MUHARRIK: Jurnal Dakwah dan Sosial, 2021)
In marriage, the two ethnic cultures of each individual will often meet to maintain the harmony of the family and to prevent the conflict of women in the dominant role. This research question is about how the role of Minangkabau women is to handle various forms of conflict that may arise due to cultural differences in a marriage. The couple had the process of adapting to the cultural values of the partner's origin to each other. The data collection methods include in-depth interviews and observations by interviewing 23 Minangkabau women from other ethnic groups. The Minangkabau women make six strategies to perpetuate their household: 1). The Minangkabau woman chooses a Javanese male to serve as her husband. 2). The Minangkabau woman has independence in determining her partner because it meets during the wander. 3). After marriage, the Minangkabau woman will bring her husband to live in the West Sumatra area. 4). Most Minangkabau women like husbands who want to contribute to the wishes of their wives. 5). The language used after marriage is the Minangkabau language. 6). Minangkabau culture is dominant and applied in children's foster patterns. This article concludes that cultural constructions have given directions for Minangkabau women to defend their families while preventing vulnerable conflicts in interethnic marriages.